Marketing Strategy 4.0 Using Internet of Things (IoT) Technology in the Cattle Breeding Industry: Case Study of PT. Goopo Innovation Indonesia - Doddy Dewayadi; Benny Ranti; Alfred Inkiriwang; Marisi Pakpahan (International Journal Business, Management and Innovation Review, 2024)
This research is a case study that analyses the 4.0 marketing strategy with the use of Internet of Things (IoT) technology in the cattle farming industry, with a focus on PT Goopo Inovasi Indonesia. The background of this research is the rapid development of digital technology and changes in consumer behaviour in the Industry 4.0 era, which encourage cattle farming companies to adopt new marketing strategies. PT Goopo Inovasi Indonesia, as a pioneer in this industry, faces the challenge of integrating IoT technology into its marketing strategy. The theories used in this research include the Marketing 4.0 concept developed by Philip Kotler, as well as theories related to the Internet of Things (IoT) and its application in the livestock industry. This research also refers to models of digital marketing strategies and innovation management. The research method used is a qualitative approach with a case study design. Data were collected through in-depth interviews with the management of PT Goopo Inovasi Indonesia, direct observation, and analysis of company documents. Data analysis was conducted using thematic analysis techniques and data source triangulation. The results showed that the implementation of marketing strategy 4.0 with the use of IoT at PT Goopo Inovasi Indonesia has increased productivity, operational efficiency and company competitiveness. The utilisation of IoT in livestock health monitoring, feed management, and product tracking has increased consumer confidence and opened up new market opportunities. However, the research also identified challenges in terms of technology investment and human resource development. The conclusion of this study confirms that the integration of 4.0 marketing strategies and IoT technology has significant potential to transform the cattle farming industry. PT Goopo Inovasi Indonesia has successfully utilised these technologies to increase the added value of its products and build stronger relationships with consumers. Recommendations for further research include long-term impact analysis and comparative studies with similar companies in different countries.